2008
DOI: 10.1098/rspb.2008.0679
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale cospeciation betweenBrachycaudusandBuchnera aphidicola: bacterial genome helps define species and evolutionary relationships in aphids

Abstract: Aphids harbour an obligatory symbiont, Buchnera aphidicola, providing essential amino acids not supplied by their diet. These bacteria are transmitted vertically and phylogenic analyses suggest that they have 'cospeciated' with their hosts. We investigated this cospeciation phenomenon at a fine taxonomic level, within the aphid genus Brachycaudus. We used DNA-based methods of species delimitation in both organisms, to avoid biases in the definition of aphid and Buchnera species and to infer association pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
115
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 60 publications
8
115
0
1
Order By: Relevance
“…For the few changes observed, mitochondrial sequences exhibit good congruence with Buchnera-Ap phylogenies (Fig. S2), consistent with other evidence supporting strictly maternal inheritance of Buchnera and mitochondrial genomes in aphid lineages (24)(25)(26)30). Similarly, sequence variation among pea aphid biotypes appears to be very low for nuclear genomes, even for noncoding regions (22), preventing any informative comparison with maternal phylogenies.…”
Section: Most Pea Aphid Biotypes Are Associated With Distinct Buchnersupporting
confidence: 63%
See 1 more Smart Citation
“…For the few changes observed, mitochondrial sequences exhibit good congruence with Buchnera-Ap phylogenies (Fig. S2), consistent with other evidence supporting strictly maternal inheritance of Buchnera and mitochondrial genomes in aphid lineages (24)(25)(26)30). Similarly, sequence variation among pea aphid biotypes appears to be very low for nuclear genomes, even for noncoding regions (22), preventing any informative comparison with maternal phylogenies.…”
Section: Most Pea Aphid Biotypes Are Associated With Distinct Buchnersupporting
confidence: 63%
“…This low sequence variation and the unknown mutation rates for these genetic markers have hindered estimation of the age of the pea aphid complex, however. Buchnera aphidicola, the obligate bacterial endosymbiont of aphids, shows strict maternal inheritance and thus phylogenetic relationships that track host matrilines (female lineages) (24)(25)(26). Buchnera of pea aphids (hereinafter called Buchnera-Ap) also undergoes a very high mutation rate, which enables dating of recent divergences (27).…”
mentioning
confidence: 99%
“…Mapping traits of the mutualists and non-mutualist relatives on time-calibrated phylogenies has proved a powerful approach to unveil the temporal and geographical origin of mutualisms. A finding of co-phylogenetic studies of mutualisms is that co-speciation is rare (reviewed in [4]) and restricted to a few symbioses, especially those with vertical transmission, such as Buchnera bacterial endosymbionts and aphids [5][6][7]. Co-speciation in mutualistic partnerships that do not involve vertical transmission may exist in some obligate systems-for instance figs and their wasp pollinators as suggested by matching divergence times, although occasional wasp switches to other figs have been documented [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ML single-threshold model usually provides a significantly better fit to the data than the null model (e.g. Pons et al 2006;Fontaneto et al 2007;Ahrens, Monaghan & Vogler 2007;Barraclough et al 2009;Jousselin et al 2009;Leliaert et al 2009;Monaghan et al 2009;Bode et al 2010;Powell et al 2011), but the ML multiple-threshold model usually does not provide a better fit to the data than the ML single-threshold model (personal observation).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have shown that this approach can identify genetic clusters that generally correspond with existing classification schemes (Monaghan et al 2009) and highlight patterns of cospeciation between an endosymbiont and its host (Jousselin, Desdevises & Coeur d'acier 2009) while also performing better than operational clustering approaches at accounting for the environmental associations of taxa (Powell et al 2011). The procedure estimates lineage birth rates associated with both Yule diversification (speciation events; Yule 1924) and neutral coalescent (merging of lineages within a population; Kingman 1982) processes from a multispecies coalescent tree, calculating the likelihood assuming a threshold age between these processes at each node in the phylogeny.…”
Section: Introductionmentioning
confidence: 99%